Portable radiation monitoring system on the base of CdWO₄ scintillator - Kosmyna, M.B.; Nazarenko, B.P.; Puzikov, V.M.; Shekhovtsov, A.N.; Grinyov, B.V.; Borodenko, Yu.A.; Selegenev, Ye.M.; Ryzhikov, V.D.; Piven, L.A.; Tarasov, V.A.; Kozmin, Yu.S.; Belogub, V.V.; et al. (Functional Materials, 2009)
A portable high-sensitivity monitor for the detection of radioactive materials is developed and manufactured on the base of CdW0₄ scintillation crystal. The monitor has an independent power supply which provides continuous operation at least during 120 hours.